2019
DOI: 10.1136/rapm-2018-000031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of programmed intermittent bolus infusion and continuous infusion for postoperative patient-controlled analgesia with thoracic paravertebral block catheter: a randomized, double-blind, controlled trial

Abstract: Background and objectivesIn this randomized, double-blind, controlled study, we hypothesized that programmed intermittent bolus infusion (PIBI) of local anesthetic for continuous paravertebral block (PVB), combined with patient-controlled analgesia (PCA), provided better pain control, better patient satisfaction, and decreased in local anesthetic consumption when compared with a continuous infusion (CI) combined with PCA, after video-assisted thoracoscopic unilateral lung resection surgery.MethodsPreoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 21 publications
(10 reference statements)
3
49
1
Order By: Relevance
“…For example, Hillegass et al showed preferable effects of PIB for femoral block in pain scores and opioid requirements [18]. Other researchers have shown that PIB for thoracic paravertebral block produced wider dermatomal sensory blockade and improved analgesia [19][20][21]. However, benefits of PIB on abdominal wall blocks have not been apparent [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hillegass et al showed preferable effects of PIB for femoral block in pain scores and opioid requirements [18]. Other researchers have shown that PIB for thoracic paravertebral block produced wider dermatomal sensory blockade and improved analgesia [19][20][21]. However, benefits of PIB on abdominal wall blocks have not been apparent [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intermittent boluses of local anesthetic have attracted attention due to the development of devices with programmed delivery and have been used to produce wider sensory blockade and better analgesia compared with continuous basal infusion with epidural analgesia for labor [15,16] and some peripheral nerve blocks [17][18][19][20][21]. Since QLB is a fascial compartment block where a large volume of local anesthetics producing a wide spread is preferable, it is reasonable to presume that intermittent boluses contribute to maintaining the range of cutaneous sensory blockade and, thus, result in better analgesia compared with the same volume using continuous basal infusion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the use of coiled catheters reduces the risk of an epidural catheter position 5–8. In a recent study, application of intermittent boli via a catheter was superior to a continuous infusion in terms of the analgesic effect 17…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical evidence to support this hypothesis is currently inconclusive. Chen et al demonstrated that hourly PIB in the thoracic paravertebral catheters for unilateral videoassisted lung resection was superior to CI by decreasing the need for additional patient controlled doses of local anesthesia, reduced pain scores, and improved patient satisfaction [4]. On the contrary, a study by Català et al demonstrated that PIB provided inferior pain control in comparison to a CI in a thoracic PVB catheter, but the pulsed interval was six hours [5].…”
Section: Discussionmentioning
confidence: 99%